EFFECT OF COVID-19 LOCKDOWN ON SPORTS PERFORMANCE PARAMETERS OF COMPETITIVE ATHLETES - Rupak K. Singh; Jayant Rastogi; Chandra Sekara Guru; Varad V. Apte; Karuna Datta; Atul Sharma (Scientific Publishing House. NSA Press, 2022)
Background: Nationwide lockdown was enforced due to the spread of the new Coronavirus-19. This resulted in cessation of all sports training across the country, including elite athletes. This COVID-19 lockdown was hypothesized to result in detraining effects on elite athletes. Aim: We aimed to study the impact of COVID-19 lockdown on athletes' physiological and anthropometric sports performance parameters. Methodology: Seventy-five athletes (age: 23.25 ± 3.9 years, training experience 7.49 ± 3.5 years) from different sports participated voluntarily. International Physical Activity Questionnaire was used to grade home-based non-supervised physical activity undertaken during COVID-19 lockdown (137.81 ± 39.20 days). We compared the measured anthropometric, aerobic, and anaerobic performance parameters post-lockdown with pre-lockdown competitive phase recordings using Kruskal Wallis non-parametric test. Parameters were expressed as mean ± SD with level of significance fixed at p < .05. Results: Statistically significant reduction of 33.28% was observed in aerobic capacity post- COVID-19 lockdown (p = .01). We did not find any statistically significant variation in the other anthropometric and physiological performance parameters, namely weight (↑17.50 %), body mass index (↑20.69 %), body fat mass (↑20.76 %), waist (↑21.07 %), hip (↑19.13 %), waist: hip ratio (↑10.71 %), peak power (↑11.32 %) and mean power (↑5.17 %). Conclusions: We found that the athletes exhibited generalized detraining features despite maintaining home-based physical activity. Compared to other performance parameters, there was a significant decrease in the aerobic capacity post-lockdown. This shows the importance of incorporating an indoor-based supervised program including aerobic exercises to guide and monitor athletes. Practical Implications: Off-season/home confinement requires a remotely supervised tailored exercise program with optimal stimuli to maintain training adaptations. Awareness and incorporation of these findings would aid coaches and trainers in designing training programs to promote athletes' injury-free gradual return to sports.